A relação terapêutica a partir da Daseinsanalyse de Medard Boss - Leça, Ana Luísa Rocheteau Antonelli (2024)
This research has as its theme the therapeutic relationship from Medard Boss's Daseinsanalyse and seeks to present its characteristic elements developed by the author throughout moments of the psychotherapeutic process of the case "The patient who taught the author to see and think in a different way", known as "The case of Dr. Cobling". To this end, a brief presentation of the Bossian biography and the aforementioned case was made – and then the inferred contributions were presented. A presentation was also made by the Brazilian Association of Daseinsanalyse, as well as its members who have published works on the therapeutic relationship and their respective contributions. It is considered that a genuine human relationship is at stake, from which the patient's changes in the psychotherapeutic process can be favored